"You have Endometriosis": Making Menstruation-Related Pain Legitimate in a Biomedical World. Issue 8 (3rd July 2019) - Wright, Kallia O.
ABSTRACT: In this essay, the author reflects on how biomedical and gendered perceptions of reproductive health can impact an illness experience. Using a narrative lens, she relays the frustration of attempting to have her excessive menstrual pain legitimated and treated when loved ones and medical professionals trivialized it and refused to let her take on the sick role. She recounts incidents that demonstrate the embedded and limiting persistence of gendered perceptions of pain. In the end, she argues that only through strong patient self-advocacy and knowledge can one rewrite the social scripts assigned to how women cope with menstrual pain.